IDENTIFIKASI TUMBUHAN PAKU YANG BERPOTENSI EPIFIT PADA BATANG TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Jusri Jusri; Nilda Yanti; Henny Poerwanty; Sofyan Sofyan (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2022)
In efforts to increase the production and productivity of oil palm, one of which is proper weed management, namely controlling ferns that have epiphytic potential on oil palm trunks. The purpose of this paper is to determine the types of ferns that have the potential as epiphytic plants on stems. Oil palm plantations, as well as identifying the effects on oil palm plantations. In addition, to determine which ferns have a higher population in oil palm plantations, PT. XIV Nusantara Plantation Unit. Keera-Maroangin Gardens. This paper is expected to be useful information material for companies in carrying out maintenance and efforts to increase production and productivity in oil palm plantations. The method used was purposive sampling which was carried out on TBM2, TBM3, and TM by collecting data on the types of epiphytic ferns, the number of populations and their effects. The types of ferns that were found to have epiphytic potential on oil palm trunks were 8 species from 3 types of families, namely, harupat ferns (Dryopteridaceae), squirrel ferns (Davalliaceae), squirrel toe ferns (Davalliaceae), wart ferns (Polypodiaceae), staghorm ferns. (Polypodiaceae), dragon scale spikes (Polypodiaceae), squirrel head spikes (Polypodiaceae), sword cylindrical spikes (Polypodiaceae). Of the 8 species of ferns found, the most common species found in the 3 plots was the harupat fern with a total of 732 populations spread in groups throughout the plot, while the least common species was the wart fern with a total of 22 populations that spread regularly.